PENGARUH PENGALAMAN KERJA, MOTIVASI DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN PT. PLN (Persero) ULP BERASTAGI - Girsang, Olpia Ulan Dari; Tinambunan, Anitha P. (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2022)
This study aims to examine and analyze the effect of work experience, motivation and work ability on the performance of employees of PT. PLN (Persero) ULP Berastagi. The population in the research amounted to 42 people, due to the small number of populations, the researcher used the entire of the population as the sample. Data was collected through documentation studies, distributing the questionnaires and interviews. Analysis of the data in this research using SPSS version 23. The sampling technique that used is the saturated sampling method. The analytical technique that used in this research is multiple linear regression analysis, t test, F test and coefficient of determination but first, the validity and reliability tests are carried out.. From the results of the partial test, the t-test value for the Work Experience variable is 3.296> ttable 1.68595 with a significance level of 0.002 < (0.05) so that, H0 is rejected and H1 is accepted. It means, work experience has a positive and significant effect on employee performance. The t-test value for the variable motivation is 4.212> t-table 1.68595 with the level of significance of 0.000 < (0.05) so that H0 is rejected and H1 is accepted. It means, motivation has a positive and significant effect on employee performance and the t-test value for the Workability variable is 2.493> ttable 1.68595 with a significance level of 0.017 < (0.05) so that H0 is rejected and H1 is accepted. It means, work ability has a positive and significant effect with the performance of employees of PT. PLN (Persero) ULP Berastagi.The result of the discussion, it is obtained that the multiple linear regression equation is Y = 3.803 + 0.299X1 + 0.491 X2 + 0.269X3 + e. The results of the analysis show that work experience, motivation and work ability have a positive effect on employee performance at PT. PLN (Persero) ULP Berastagi. The coefficient of determination of 0.752 is equal to 75.2%. It means that the Employee Performance variable can be explained by the variables of work experience, motivation and work ability of 75.2%, the rest 24.8% is explained by other variables which not included in this research.